Malawi faces a food crisis: Why plans to avert hunger aren’t realistic and what can be done - De Weerdt, Joachim; Duchoslav, Jan (The Conversation, 2024)
Malawi is heading towards a severe food crisis later this year. Drought brought on by the El Niño weather pattern has affected the harvest of maize, the staple food grown by nine out of 10 farming households in the country.